2018
DOI: 10.1111/evj.12969
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic identification of atrial‐related structures and vessels in horses validated by computed tomography of casted hearts

Abstract: Important cardiac structures and vessels, even the different pulmonary veins, could be identified on standard and nonstandard ultrasound images in adult horses. This knowledge is important to guide and develop interventional cardiology and might be useful for diagnostic and therapeutic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…The atrial rate (depolarisations per minute) was calculated as 60 divided by the total length of 20 successive depolarisations on the surface ECG multiplied with 20. As part of a standard procedure TVEC started with ultrasound guided placement of a bipolar sensing/pacing electrode (bipolar intracardiac electrode) d at the intervenous tubercle in the right atrium in the standing horse [16]. Surface ECG and intra-atrial electrogram were recorded simultaneously with a modified Televet 100 device b [17].…”
Section: Electrocardiographymentioning
confidence: 99%
“…The atrial rate (depolarisations per minute) was calculated as 60 divided by the total length of 20 successive depolarisations on the surface ECG multiplied with 20. As part of a standard procedure TVEC started with ultrasound guided placement of a bipolar sensing/pacing electrode (bipolar intracardiac electrode) d at the intervenous tubercle in the right atrium in the standing horse [16]. Surface ECG and intra-atrial electrogram were recorded simultaneously with a modified Televet 100 device b [17].…”
Section: Electrocardiographymentioning
confidence: 99%
“…Briefly, the sonographers modified the right parasternal long axis view as follows: to visualize the third pulmonary venous ostium and RPA, the sonographers moved the ultrasound probe slightly apically and angled it dorso-cranially, to obtain a somewhat oblique view of the heart base (Fig 1). To conserve nomenclature that has been adopted in companion animals, we refer to the third pulmonary venous ostium as the right pulmonary vein (RPV) throughout the remainder of this manuscript, as this ostium receives blood from the largest part of the right lung [4,5], and is analogous to the right pulmonary vein in dogs and cats [68].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, investigators have described the echocardiographic visualization of equine pulmonary vein ostia [4,5]. These authors suggested that the size and flow patterns of the pulmonary veins might help the assessment of cardiovascular disease in horses [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Using casting resins to create negative contrast is also an interesting approach to study hollow organs and enclosed spaces. Vandecasteele et al () injected the lumen of the equine heart and greater vessels with self‐expanding polyurethane foam (ordinary construction foam found in every DIY shop). After curing, the corrosion step was omitted, and the cast and surrounding tissues were directly scanned by CT. As the PU foam mainly consists of entrapped gas, CT images of the specimen showed a virtually empty (radiolucent) but fully distended lumen.…”
Section: Choice Of Casting Mediummentioning
confidence: 99%